2020
DOI: 10.1088/1402-4896/abd057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transverse magnetic field on the properties of laser ablation produced nickel oxide nanoparticles

Abstract: Influence of transverse magnetic field on the nickel produced plasma plume and structural and optical properties of nickel oxide nanoparticles produced by pulsed laser ablation (PLA) method have been investigated experimentally. Ablation container was placed between the poles of permanent magnets. Strength of external magnetic field was controlled by the distance between magnets. The direction of the magnetic field was perpendicular to the direction of laser pulse propagation. 5 samples were synthesized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The FTIR spectra, plotted in figure 9, show four different absorption bands. The bands ranging between 3700-2900 cm −1 and 1750-1500 cm −1 are attributed to the stretching ( ) n -O H and bending ( ) d --H O H vibrations of water molecules [9,51]. The presence of these bands is allocated to the tendency of the nanoparticles to physically absorb the atmospheric moisture [24].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectra, plotted in figure 9, show four different absorption bands. The bands ranging between 3700-2900 cm −1 and 1750-1500 cm −1 are attributed to the stretching ( ) n -O H and bending ( ) d --H O H vibrations of water molecules [9,51]. The presence of these bands is allocated to the tendency of the nanoparticles to physically absorb the atmospheric moisture [24].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Among the oxide-based DMS, NiO nanoparticles are of great interest due to their viability for suiting several applications such as anode material for rechargeable lithium-ion batteries [3], supercapacitors [4], photocatalysis [5], and gas sensors [6,7]. NiO is an antiferromagnetic (AFM) oxide with Neel transition temperature (T N ~523 K) above the room temperature [8,9]. In the nano regime, the magnetic properties of NiO are tuned by varying the size, as it shows superparamagnetic behavior for particles with sizes less than 31.5 nm, ferromagnetic behavior for particles with sizes less than 24 nm, and spin glass behavior with sizes less than 10 nm [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the introduction of a magnetic field enhanced the ablation rate and optical properties of NPs. Safa et al [169] experimentally investigated the effects of varying the transverse magnetic field on NiO NPs. The strength of the magnetic field is controlled by varying the distance between the magnets.…”
Section: Magnetic Field-assisted Plalmentioning
confidence: 99%
“…Regarding fractal integration, the investigation of unpredicted matrix theory, with special consideration on energy level spectrum and fractal characteristics was exploited by Sani and Behnia [47], and complex association of inductivity from length as the overall contribution of both the 2D and 3D fractal behaviors of respectively the coplanar microwave transmission lines and the W is provided by not only fractal features of CTL twodimensional surface but fractal features of three-dimensional Au grain distribution over skin depth wide was investigated by Torkhov et al [48]. Also, the JJ was observed in different contributions including the investigation of the dynamics exhibited by coupling two JJ to micro-beam [49], evaluations of the dynamics of the long 0-π JJwith applications to digital single flux quantum circuits [50], the comparison of the theoretical evaluation of quantum optical micro maser and JJ-photonics systems [51], the observations ofchaos, transient chaos, the coexistence of solutions, coexistence of attractors, and bursting oscillation just to cite some were observed in the findings of [52], the investigation of the magnetic characteristics of artificial nanoparticles via their hysteresis curves for vibrating sample magnetometerwas carried out by [53], the detail investigation of the hysteresis characteristics of the thermodynamic and magnetocaloric behaviors of a three-layer graphene-like schematic [54], and finally the investigation of the JJ with high critical-temperaturesuperconductors [55].…”
Section: Introductionmentioning
confidence: 99%